Clinicoepidemiological Profile of Severe Cutaneous Adverse Drug Reaction: A Retrospective Study - Damayanti Damayanti; Menul Ayu Umborowati; Sylvia Anggraeni; Cita Rosita Sigit Prakoeswa; Marsudi Hutomo; Hari Sukanto (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2019)
Background: Drug eruption were varied from mild to severe reaction. Few studies have assessed the severe cutaneous adverse drug reaction (SCADR), especially in the setting of general hospital. Purpose: To evaluate clinicoepidemiological profile of SCADR at Dermatology and Venereology Ward Dr. Soetomo Hospital, Surabaya, Indonesia. Methods: All SCADR patients at Dr. Soetomo Hospital, Surabaya, Indonesia in the period of January 2016 – June 2017 was evaluated. Stevens-Johnson Syndrome (SJS), Toxic Epidermal Necrolysis (TEN), Acute Generalized Exanthematous Pustulosis (AGEP), Drug Reaction with Eosinophilia and Systemic Symptoms (DRESS) and exfoliative dermatitis cases were included in the study. Results: There were 24 patients in this study, consisted of 11 SJS cases, 1 TEN case, 2 SJS/TEN-overlap cases, 10 exfoliative dermatitis cases. The mean of latent period between drug intake and onset of symptoms was 15.8 days. The most common offending drug was mefenamic acid (20.9%), followed by cefadroxil and phenytoin (each 16.7%). Antibiotics was the highest frequent offending drug-groups (62.5%), followed by non-steroid anti-inflammatory drugs (NSAIDs). Prompt withdrawal of the offending drugs, systemic corticosteroid, and supported therapy were given to all patients, which gave good results in 21/24 patients (87.5%). Conclusion: Antibiotics were the most common offending drug-groups. SCADR might give high mortality rate, but early diagnosis, prompt withdrawal of the suspected drugs, closed monitoring to evaluate complications can improve the prognosis of SCADR.